Adverse pregnancy outcomes and subsequent development of connective tissue disease in the UK: an epidemiological study. (25th March 2020) - Kither, H; Heazell, A; Bruce, IN; Tower, C; Crocker, I
Abstract : Objective: This study assessed prevalence of connective tissue disease (CTDs), systemic lupus erythematosus (SLE), antiphospholipid syndrome (APS) and antiphospholipid antibodies (aPL) in women with previous adverse pregnancy outcome compared with uncomplicated livebirths. Design: Retrospective case–control study. Setting: UK Primary Care. Population or sample: Records of women, 18 years and older, within the Clinical Practice Research Datalink (CPRD) (1 January 2000–31 December 2013). Methods: Clinical Practice Research Datalink was searched for pregnancy terms to identify adverse pregnancy outcome. Each identified case was matched to five livebirths. Main outcome measures: Diagnosis of SLE, CTD, APS or autoimmune antibodies. Poisson regression was performed to calculate relative risk ratios (RR), comparing adverse pregnancy outcome with livebirth cohorts. Results: Clinical Practice Research Datalink identified 20 123 adverse pregnancy outcomes matched to 97 323 livebirths, with a total of 875 590 person‐years follow up. Median follow up from study entry was 7.29 years (SD 4.39). Compared with women with an uncomplicated livebirth, women with adverse pregnancy outcome had an increased risk of developing CTD or autoimmune antibodies (RR 3.20, 95% CI 2.90–3.51). Risk was greatest following a stillbirth (RR 5.82, 95% CI 4.97–6.81). For CTD and SLE, the risk was greatest within the first 5 years of adverse pregnancy outcome. Risk for aPL and APS diagnosis was highest ≥5 years from adverse pregnancy outcome. Conclusions: Adverse pregnancy outcome is associated with increased risk of developing maternal CTD, including SLE. Either immunological factors predispose women to adverse pregnancy outcome and subsequent CTD diagnosis or, alternatively, adverse pregnancy outcome initiates autoimmune events which culminate in CTD in later life. Tweetable abstract: Stillbirth is associated with increased maternal risk of developing systemic lupus erythematosus (SLE). Tweetable abstract: Stillbirth is associated with increased maternal risk of developing systemic lupus erythematosus (SLE).